Nonpneumatic Antishock Garment Combined with Bakri Balloon as a Nonoperative "Uterine Sandwich" for Temporization of Massive Postpartum Hemorrhage from Disseminated Intravascular Coagulation - Andrea Jelks; Monica Berletti; Liliana Hamlett; Michele Hugin (Hindawi Limited, 2015)
Disseminated intravascular coagulation (DIC) is an uncommon but potentially catastrophic complication of postpartum hemorrhage. We describe two cases of massive postpartum hemorrhage complicated by DIC that were successfully temporized with combined use of the Bakri balloon and nonpneumatic antishock garment (NASG) during massive transfusion. In the first case, a healthy, term gravida underwent emergent cesarean for fetal bradycardia during labor induction. 10 minutes after completion of surgery, brisk vaginal hemorrhage of nonclotting blood from fulminant DIC resulted in maternal shock. A Bakri balloon and NASG were placed during massive transfusion, resulting in rapid maternal stabilization. In the second case, a healthy, term gravida suffered an amniotic fluid embolism during labor requiring emergent cesarean delivery and complicated by cardiac arrest with successful resuscitation. Postoperative rapid uterine bleeding from DIC was treated with a Bakri balloon and NASG, stabilizing the patient during massive transfusion. Neither patient required further surgical procedures. NASG combined with Bakri balloon may serve as a valuable nonoperative treatment or temporization option in cases of massive postpartum hemorrhage complicated by coagulopathy such as these. Further study of the utility of NASG in high-resource settings is warranted.